Ethanol extract from Ziziphus nummularia stem inhibits MCF-7 breast cancer cell proliferation through TP53 regulating kinase (TP53RK)-mediated p53 activation: In silico and genes expression investigations - Elya, Berna; Rosmalena, Rosmalena; Fajrin, Ajeng M.; Tedjo, Aryo; Ramadanti, Nur A.; Azizah, Norma N.; Hashim, Najihah BM. (Narra Sains Indonesia, 2025)
The p53 signaling pathway plays a critical role in regulating the cell cycle, apoptosis, and senescence, making it a key target in cancer research. The aim of this study was to investigate the effects of an ethanol extract from the stem of Ziziphus nummularia on the proliferation and expression of genes involved in the p53 pathway in MCF-7 breast cancer cells. To achieve this, real-time quantitative PCR (RT-qPCR) was used to evaluate the mRNA expression of downstream genes linked to cell cycle and senescence, including CycE or CCNE1, RBL1, and E2F1. Molecular docking simulations using Molegro Virtual Docker (MVD) were also performed to assess the potential inhibitory activity of metabolite compounds from Z. nummularia stem against p53-regulating kinase (TP53RK). The results showed that the IC50 value of Z. nummularia stem ethanol extract against MCF-7 cells was 38.27±0.72 µg/mL. The results also revealed a reduction in the expression of downstream genes linked to cell senescence and the cell cycle: CycE or CCNE1 (p=0.011), RBL1 (p=0.008), and E2F1 (p=0.005), which was observed through RT-qPCR analysis of mRNA expression. This fact indicated that the inhibitory effects on proliferation by the ethanol extract of Z. nummularia stem might occur via pathways associated with cell senescence and cell cycle arrest. Molecular docking results of metabolite compounds from Z. nummularia stem suggested that squalene (Rerank score -112.70 kJ/mol), and nummularine B (Rerank score -110.68 kJ/mol) had potential as TP53RK inhibitors. These Rerank scores were smaller compared to the Rerank score of adenyl-imidodiphosphate (AMP-PNP), which was the native ligand of TP53RK, as confirmed by molecular dynamics analysis. These in silico results were confirmed by the decrease in p21 (CDKN1A) mRNA expression. In conclusion, the anti-proliferative effects of the ethanol extract from Z. nummularia stem on breast cancer cells occurred by affecting cell cycle-related genes and inhibiting apoptosis protection mediated by overexpression of p21 (CDKN1A) through p53 activity.